Matrix analyses of pharmaceutical products for the years 2017 to 2019 among public health facilities in Hadiya zone, Ethiopia: a cross-sectional descriptive study - Tamirat Yohannes; Bekele Boche; Nimona Birhanu; Tadesse Gudeta (BMC Health Services Research, 2022)
Abstract Background To date, global healthcare spending becomes a primary concern, and pharmaceutical costs are the main drivers. The issue is more pressing in developing countries like Ethiopia. However, there is a scantiness of comprehensive data on inventory control practices in health facilities. This study, therefore, aimed to assess the criticality, financial value, and consumption patterns of pharmaceuticals using inventory matrix analyses and explore the related challenges. Methods A cross-sectional study supplemented with qualitative assessments was carried out from December 2020 to January 2021 in public health facilities. Three hospitals and 14 health centers were proportionally selected using a simple random sampling technique. Self-administered questionnaires and review of logistics documents and databases like Dagu-Facility were used to obtain the quantitative data. The data were analyzed using excel spreadsheets and SPSS version 23. We gathered the qualitative data through face-to-face in-depth interviews. Results The facilities spent 66,312,277.0 Ethiopian birrs to procure 518 pharmaceuticals between 2017 and 2019. Of the total products, 68 (13.1%) belonged to class A and 353 (68.1%) belonged to class C. Among 427 items identified by VEN analysis, 202 (47.3%) were vitals, and 201 (47.1%) were essential products making the highest proportions. Cross-tabulations of ABC and VEN showed that 230 (53.9%) items formed category I, representing 84.3% of total expenditures. Sterile surgical gloves #7.5, amoxicillin capsules, examination gloves, and 40% dextrose injection were among the top-ten high-value closing inventories, accounting for 21% of class X items. The fast-moving items were the most prevalent in all years, accounting for more than 45%, and shared the maximum expenditure, up to 90%. Scarcity of infrastructure and skilled human resources, shortage of pharmaceuticals and problems with suppliers, and management issues were the major challenges in the health facilities. Conclusion Most of the items identified by ABC-VEN and FSN-XYZ were Category one, i.e., mainly vital costly products and a few fast-moving items with high closing inventory values, respectively, suggesting close supervision. However, several issues became impediments. Hence, facilities should alleviate the bottlenecks and monitor the stock status to prevent theft and stock out.